Liquefied petroleum gas or biomass for cooking and effects on birth weight - Clasen, TF; Chang, HH; Thompson, LM; Kirby, MA; Balakrishnan, K; Díaz-Artiga, A; McCracken, JP; Rosa, G; Steenland, K; Younger, A; Chen, Y; Aravindalochanan, V; et al. (Massachusetts Medical Society, 2022)
BACKGROUND: Exposure during pregnancy to household air pollution caused by the burning of solid biomass fuel is associated with adverse health outcomes, including low birth weight. Whether the replacement of a biomass cookstove with a liquefied petroleum gas (LPG) cookstove would result in an increase in birth weight is unclear.